IUGS RECLASSIFICATION OF THE HIGH-MG AND PICRITIC VOLCANIC ROCKS - Le bas M.J. (My University, 2000)
The 1989 IUGS classification of the igneous rocks for the high-Mg and picritic volcanic rocks has been revised. Instead of an 18 wt % MgO minimum limit being applied for all high-Mg and picritic volcanic rocks, that is now applicable only to the high-Mg rocks such as komatiite and meimechite. The minimum MgO requirement for picrite is reduced to 12 wt %. The SiO2 former boundary figure between boninite and komatiite–meimechite–picrite, which was 53 wt %, is reduced to 52 wt %, and the total alkali content for komatiite and meimechite is increased to 2% and for picrite to 3%.